Morality and self-control: the role of binding and individualizing moral motives - Silver, Eric (Deviant behavior, 2021)
The notion that morality and self-control are linked is deeply rooted in Western scholarly and religious traditions, yet few studies have examined this notion empirically. To fill this gap, we employ a pluralistic moral framework and data from four independently gathered samples to examine the relationship between morality and self-control. We hypothesize that people with higher levels of morality (measured as individualizing and binding moral motives) will exhibit higher levels of self-control, and that these moral motives will mediate the association between prior socialization and self-control. Consistent with our hypotheses, we find that the individualizing moral motive is positively associated with self-control, net of demographic and parenting measures, and that it mediates the association between prior socialization and self-control. However, contrary to our hypotheses, we find that the binding moral motive is inversely associated with self-control. These divergent results, found across four data sets, indicate that the relationship between morality and self-control is more complex than previously understood, and highlight the importance of expanding the conceptualization of morality to include both individualizing and binding moral motives in order for a more complete understanding of the relationship between morality and self-control to be obtained.